BEPS Pillar Two Implementation in ASEAN: Tax Competition, FDI Sensitivity, and Fiscal Implications for Indonesia - Islamiati Hidayah (Islamic Economics Journal, 2026)
This paper presents a systematic empirical analysis of Corporate Income Tax (CIT) rate competition and Pillar Two adoption dynamics across eleven ASEAN nations over the period 2005–2024. Using an unbalanced panel dataset compiled from the International Monetary Fund, World Bank, OECD, and UNCTAD, we document a statistically significant race-to-the-bottom in statutory CIT rates, with the ASEAN unweighted average declining from 28.5% in 2005 to 20.9% in 2024, a structural downward trend of approximately 0.44 percentage points per year (R² = 0.90). For Indonesia specifically, we estimate a negative semi-elasticity of FDI inflows with respect to the CIT rate of −0.155 (significant at the 1% level), implying that each one-percentage-point reduction in the statutory rate is associated with a 15.5% increase in inward FDI, assuming the tax rate variable is entered in percentage-point units. Analysis of Country-by-Country Reporting (CbCR) data for Indonesia (2016–2022) reveals that effective tax rates (ETRs) paid by multinational enterprises (MNEs) fell below the 15% global minimum in at least two observed years. However, applying GloBE-compliant micro-data adjustments, including the Substance-Based Income Exclusion (SBIE) and the EUR 750 million consolidated revenue threshold, substantially reduces projected top-up tax revenue from aggregate estimates of USD 43.9 million (2016) to approximately USD 4.8 million, correcting a systematic optimism bias in earlier projections. Indonesia's implementation of Pillar Two via PMK-136/2024, effective January 2025, positions it among the five ASEAN early adopters alongside Vietnam, Malaysia, Thailand, and Singapore, while Cambodia, Laos, Myanmar, the Philippines, Brunei, and Timor-Leste have not yet implemented Pillar Two. The resulting regulatory asymmetry poses material risks of investment diversion. We find that Indonesia's dual anti-avoidance architecture (CFC rule and interest limitation rule), which is unique within ASEAN, provides a meaningful fiscal buffer. Still, its structurally thin tax-to-GDP ratio (10.4% average, 2005–2024) limits fiscal space to absorb FDI contraction. The paper provides a detailed regulatory breakdown of PMK-136/2024, the transfer pricing framework under PMK-172/2023, and the Coretax digitalisation initiative. It concludes with concrete policy recommendations for the Directorate General of Taxes (DGT) to manage the trade-off between Pillar Two compliance and regional investment competitiveness. Although the empirical dataset covers the period 2005–2024, several developments occurring in early 2025 are discussed as part of the implementation context and policy environment rather than as part of the econometric estimation sample.